Pelatihan E-Commerce dan Marketplace Bagi Masyarakat Muda Desa Dasan Baru Kediri - Valian Yoga Pudya Ardhana; M. Dermawan Mulyodiputro (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
Information technology that continues to develop has a positive impact on all sectors of the economy to increase the competitiveness of business people. Online business or e-commerce is a current trend that cannot be denied as an opportunity for business people by utilizing internet media to carry out their activities anywhere and anytime without being limited by place or time. Advances in technology today can take advantage of the role of the internet and mobile devices that are owned to develop businesses that are owned online so as to enable achieving a wider market share. Therefore, e-commerce and marketplace training was conducted in Dasan Baru Village, Kediri, where the participants were young people who live in Dasan Baru Village. The purpose of this training activity is that young people in the Dasan Baru Kediri Village area have knowledge of online business concepts and utilize internet-based marketplaces to maximize their business marketing. With the training carried out, the participants can practice directly on their respective computers or gadgets, about the features on the marketplace, and the suggestions for progressing online businesses that are given. The implementation of this community service received a positive response from both the participants and the people of Dasan Baru Village in general. Participants took part in the training enthusiastically and were motivated to do business online following the current trend of the digital era.